A comparison of soil structure and atrazine efficacy between two tillage practices - Wardak, Daniel (2025)
Agricultural soil management practices, such as zero-tillage (ZT) and ploughing, play critical but contrasting roles in determining soil structure and function. These practices primarily and differentially influence soil porosity; ploughing generates an increased but ephemeral inter-aggregate macroporosity whereas ZT promotes a more stable biologically driven pore network architecture to develop over time. However, the influence of alternative pore network characteristics to solute transport and agrochemical efficacy remains unclear. Using a combination of X-ray Computed Tomography and solute breakthrough experiments, this thesis investigates the role of the imaged soil pore network to preferential transport and efficacy of the herbicide atrazine across a variety of zero-tilled and ploughed soils. Here, we show that large vertically oriented cylindrical macropores were ubiquitous across zero-tilled soil but less present in ploughed, with zero-tilled soil demonstrating a doubled preferential transport speed which correlated with increasing pore thickness and decreasing connectivity. Additionally, atrazine efficacy was significantly reduced in ZT soil compared with ploughed soil, with efficacy correlating with pore thickness and connectivity in low and medium application rates, which was dependent on formulation, suggesting different mechanisms of transport. Reduced atrazine efficacy and increased preferential transport under ZT is problematic considering the inherent reliance on chemical methods for weed control in this practice. Investigating a land-use specific formulation approach for further agrochemical development may be beneficial.